Determinants Factors of Vasectomy Method Selection - Esti Yunitasari; Retnayu Pradanie; Hardiansyah Hardiansyah (Jurnal Ners, 2017)
Introduction: The level of male participation in family planning by choosing vasectomy in East Lampung region Pekalongan health centers is still low, although the success rate of vasectomy as family planning is very high. This study aimed to explain the factors related to the men’s choice of vasectomy in the Pekalongan health center East Lampung.Methods: This study used an analytical study design with a cross-sectional approach. Samples were 117 men in reproductive age gathered by using purposive sampling. The independent variables were knowledge, attitudes, parity, age, availability of health resources and infrastructure, health education, attitude and behavior of health care workers and family support. The dependent variable was the men’s participation in vasectomy as family planning. Data were retrieved using questionnaires and statistically analyzed using Chi-Square test.Results: Factors affecting the selection of vasectomy as family planning in men with reproductive age were an attitude (p=0,020), parity (p=0.022), age (p=0,021), the availability of health resources and health infrastructure (p=0.018), and family support (p=0.011). However, the knowledge, health education, and the attitudes and behavior of health workers did not affect the selection of vasectomy as family planning.Discussion: Public Health Centres are expected to build a family planning services, especially for vasectomies, such as the provision of vasectomy facilities which can reach the community and the establishment of cadres for male birth control.